Continuous versus intermittent noninvasive blood pressure measurement in patients with shock in prehospital emergency medicine - a single-center prospective pilot trial - Katzenschlager, Stephan; Heck, Raphael; Kaltschmidt, Nikolai; Weilbacher, Frank; Weigand, Markus A.; Popp, Erik; Dietrich, Maximilian (Scandinavian journal of trauma, resuscitation and emergency medicine, 2025)
Shock is a critical and potentially life-threatening clinical state characterized by circulatory insufficiency and impaired micro- and macrocirculation. Rapid detection and initiation of therapy are essential for patient outcomes. In prehospital emergency medicine, assessment tools are limited, and intermittent noninvasive blood pressure (iNIBP) monitoring is the current standard of care. Recent findings suggest that this method may miss episodes of relevant hypotension. Continuous noninvasive blood pressure (cNIBP) and tissue oxygenation (StO2) measurements could improve the time to detection of shock.